2007
DOI: 10.1038/sj.ijo.0803571
|View full text |Cite
|
Sign up to set email alerts
|

Increasing body mass index from age 5 to 14 years predicts asthma among adolescents: evidence from a birth cohort study

Abstract: Background:Obesity and asthma are common disorders, and the prevalence of both has increased in recent decades. It has been suggested that increases in the prevalence of obesity might in part explain the increase in asthma prevalence. This study aims to examine the prospective association between change in body mass index (BMI) z-score between ages 5 and 14 years and asthma symptoms at 14 years. Methods: Data was taken from the Mater University Study of Pregnancy and its outcomes (MUSP), a birth cohort of 7223… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 22 publications
4
66
0
1
Order By: Relevance
“…19 There was insufficient data to combine the results from studies of dose-response associations; 3 studies for wheeze revealed a significant dose-response effect, 28-30 and 3 studies for asthma [31][32][33][34] revealed a significant dose-response effect; the significance could not be determined for 1 study, although the results did demonstrate increasing ORs. 32 However, 2 of the above studies also demonstrate a nonsignificant trend.…”
Section: Household Smokingmentioning
confidence: 75%
“…19 There was insufficient data to combine the results from studies of dose-response associations; 3 studies for wheeze revealed a significant dose-response effect, 28-30 and 3 studies for asthma [31][32][33][34] revealed a significant dose-response effect; the significance could not be determined for 1 study, although the results did demonstrate increasing ORs. 32 However, 2 of the above studies also demonstrate a nonsignificant trend.…”
Section: Household Smokingmentioning
confidence: 75%
“…[9][10][11][12][13][14][15][16][17] There are also some published studies that have not found any association between asthma and overweight in children. 19,27 These studies have a cross-sectional design in common; a prospective design is much more suitable for suggesting risk and direction of causation.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies suggest that overweight (most often measured as high BMI) at various ages increases the risk of asthma in childhood. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Despite this, the nature of the association between overweight and asthma is not completely understood, and only 1 study has looked at change in BMI status during childhood and the risk of asthma. 17 Results from a Dutch birth cohort showed that children with high BMI at age 6 to 7 years had an increased risk of asthma symptoms at age 8 years, whereas children with high BMI earlier in life and with normal weight at age 6 to 7 years did not.…”
mentioning
confidence: 99%
“…Mannino et al 37 showed that boys but not girls with body mass index (BMI) 485th percentile were at an increased risk of developing asthma later on. Recently Mamun et al 38 found that increased BMI z-scores between the ages of 5 and 14 years were associated with increased risk of asthma symptoms in adolescence, with a stronger, although not significant, association in the males. In this study, the relationship remained robust with adjustment for a range of reasons in early-life exposure such as a child's weight at birth, length of breastfeeding, maternal lifestyle during pregnancy, as well as diet, sports and TV watching at follow-up at 14 years.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the relationship remained robust with adjustment for a range of reasons in early-life exposure such as a child's weight at birth, length of breastfeeding, maternal lifestyle during pregnancy, as well as diet, sports and TV watching at follow-up at 14 years. 38 Finally, in another study, the annual variations in BMI z-scores were significantly associated with asthma in girls. 39 Atopy is another important hallmark of childhood asthma as at least 90% of asthmatic children present clinically determined allergic sensitization.…”
Section: Introductionmentioning
confidence: 99%